Сульфидная система раннепротерозойских пород центральной части Украинского щита - Фомин, Ю.А.; Демихов, Ю.Н. (Видавничий дім "Академперіодика" НАН України, 2008)
The mineralographic and isotopic (S) sulfide peculiarities of some gold-bearing districts in the Central Part of the Ukrainian Shield are viewed. Epigenetic sulfides (pyrite, pyrrhotite, arsenopyrite) in comparison with pyrite and pyrrhotite of host rocks (Bugskaya series) mark homogeneous sulfur and a displacement of δ^34 S significances to isotope ³²S. Besides increasing the oxidation potential of mineral-forming fluids at the late metasomatism, an addition of deep sulfur at that time was possible.